DAMPAK MEDIA SOSIAL TERHADAP PARTISIPASI POLITIK PENYANDANG DISABILITAS - Indah Sulistiani; Syarifuddin (CV. Adiba Aisha Amira, 2025)
Social media has become an important tool in increasing political participation among people with disabilities. These platforms offer opportunities for people with disabilities to actively engage in political discussions, access up-to-date information, and voice their opinions more widely. However, challenges remain, including suboptimal accessibility and the presence of discriminatory content that can hinder their active involvement. Despite these obstacles, the potential of social media to empower people with disabilities in the political sphere remains significant. With collective efforts to improve inclusion and accessibility, social media can play a key role in achieving more inclusive and fair political participation.